Pengaruh Video Edukasi tentang Faktor yang Mempengaruhi Stunting Melalui Sosial Media Youtube Terhadap Pengetahuan Remaja - Alvito Zidane Pamungkas; Rini Ernawati; Enok Sureskiarti (JURNAL PENA EDUKASI, 2024)
Abstract: Stunting Stunting is a condition of failure to thrive in children under five years old caused by chronic malnutrition which is a problem in Indonesia. The aim of the research is to find out whether there is an influence of stunting education via YouTube social media on students at SMA Negeri 4 Samarinda. This research uses a quantitative research design with a Pretest - Posttest Control Group Design to compare the experimental group that was given stunting education via videos on YouTube social media with a control group that was not given intervention. The number of samples in this study was 20 students of class XI. The instrument used is a questionnaire. Test statistical analysis with the Wilcoxson Alternative Test. The result of the p-value is 0.000 because the p value <α (0.05), then Ha is accepted and H0 is rejected. This shows that the respondents' knowledge before and after being given interventions regarding stunting to students at SMA Negeri 4 Samarinda increased the average value of the respondents' knowledge. So there is a significant influence on knowledge before the intervention is given and after the intervention is given by providing stunting education.Keywords: Education, Stunting, Teenager, YoutubeAbstrak: Stunting adalah kondisi gagal tumbuh pada anak berusia dibawah lima tahun yang disebabkan kekurangan gizi kronis yang menjadi masalah di Indonesia. Tujuan dari penelitian adalah untuk mengetahui apakah ada pengaruh edukasi stunting melalui media sosial youtube pada siswa SMA Negeri 4 Samarinda. Penelitian ini menggunakan desain penelitian kuantitatif dengan with desaign Pretest – Posttest Control Grup Desaign untuk membandingkan kelompok experiment yang diberikan edukasi stunting melalui video di media sosial youtube dengan kelompok kontrol yang tidak diberikan intervensi. Jumlah sampel dalam penelitian ini adalah 20 orang siswa/I kelas XI. Instrument yang digunakan ialah kuesioner. Uji analisis statistik dengan Uji Alternatif Wilcoxson. Hasil p-value 0,000 karena nilai p<α (0,05) maka Ha diterima dan H0 ditolak. Hal ini menunjukan bahwa pengetahuan responden sebelum dan setelah diberikan intevensi mengenai stunting pada siswa dan siswi di SMA Negeri 4 Samarinda terdapat peningkatan nilai rata – rata pengetahuan responden. Sehingga ada pengaruh yang signifikan terhadap pengetahuan sebelum diberikan intervensi dan setelah diberikan intervensi pemberian edukasi stunting.Kata kunci: Edukasi, Remaja, Stunting, Youtube